Differential diagnosis of infectious skin lesions in an HIV-positive patient: A case report - Méndez, Yardany Rafael (2017)
HIV infection makes HIV carriers susceptible to develop a group of infections that would not normally be found in an immunocompetent patient. In Colombia, a total of 11,606 cases of HIV infection were reported in 2015. This paper documents the case of a patient diagnosed with HIV infection, who developed lesions typically caused by the varicellazoster virus. These vesicular lesions evolved into phlyctenas with local necrosis. Given the case presentation, the diagnosis of skin lesions in immunocompromised or HIV-infected patients becomes a challenge for health professionals when determining an etiological diagnosis, in order to establish an appropriate treatment.